Ethics of the fiduciary relationship between patient and physician: the case of informed consent - Tavakoli, Sophie; Narchi, Jonas; Kiefer, Lukas; Winkler, Eva C. (Journal of medical ethics, 2022)
This paper serves two purposes: first, the proposition of an ethical fiduciary theory that substantiates the often-cited assertion that the patient-physician relationship is fiduciary in nature; and second, the application of this theory to the case of informed consent. Patients’ decision-making preferences vary significantly. While some seek fully autonomous decision-making, others prefer to delegate parts of their decision. Therefore, we propose an ethical fiduciary theory that allows physician and patient to jointly determine the physician’s role on a spectrum from fiduciary as advisor to fiduciary as agent. Drawing on legal concepts of the fiduciary relationship and on phenomenological accounts of obligation by Lévinas and Løgstrup, our theory relies on the key attributes of trust, vulnerability and otherness. Finally, practical implications of this theory for the informed consent process are developed: we propose a preassessment of patients’ risk and value profiles as well as a restructuring of the oral consent interview and the written consent materials.